2018
DOI: 10.1021/acs.iecr.8b02999
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects of HCl Adsorption on Mg–Fe Hydrotalcite-like Oxides at 350–650 °C in Flue Gas

Abstract: Calcined Mg–Fe hydrotalcite-like compounds (HTLs), hydrotalcite-like oxides (HTOs), have shown potential performance for removing hydrochloric acid (HCl) from flue gas at medium-high temperatures. The adsorption of HCl on Mg–Fe HTOs was studied from 350 to 650 °C. The average removal efficiency of HCl on Mg–Fe HTOs is affected primarily by temperature-dependent structural changes. Structural changes in pristine and calcined HTL samples were characterized using various analytical techniques. The pyrolysis kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Over the past two decades in particular, the unique physicochemical properties of layered double hydroxides (LDHs), often known more generically as hydrotalcites, have gained considerable attention in the research community, [1][2][3][4] and industry due to their application as sorbents or catalysts, [5][6][7][8][9][10][11][12] and for the treatment of mining or other wastewaters. [13][14][15][16] The utility of LDHs stems from their tuneable functional properties that may result from the substitution of a variety of cations into the metal double hydroxide layers and anions into the interlayer spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades in particular, the unique physicochemical properties of layered double hydroxides (LDHs), often known more generically as hydrotalcites, have gained considerable attention in the research community, [1][2][3][4] and industry due to their application as sorbents or catalysts, [5][6][7][8][9][10][11][12] and for the treatment of mining or other wastewaters. [13][14][15][16] The utility of LDHs stems from their tuneable functional properties that may result from the substitution of a variety of cations into the metal double hydroxide layers and anions into the interlayer spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to developing superior adsorbents to remove HCl. Cao et al 14 prepared HCl antichlor of Ca‐Mg‐Al mixed oxides by using the coprecipitation method after being calcined at 350°C for 2 h, indicating that it has better performance than MgO, NaHCO 3 , and CaO. Wang et al 19 studied the synergistic removal effect of SO 2 , HCl, and other pollutants by viscose‐based activated carbon fibers in simulated incineration flue gas and found that the removal efficiency of HCl reached 100% during a long time 19 .…”
Section: Introductionmentioning
confidence: 99%
“…2830 Hydrotalcite-like composite is a good dechlorination adsorbent, especially in the water environment, but its dechlorination characteristics in a high-temperature gas environment are yet studied. In some literature studies, 31,32 the high-temperature dechlorination adsorbent for hydrotalcite-like materials was studied, including the preparation of the dechlorination adsorbent, adsorption test, cross-flow moving bed reactor, and numerical simulation. It was generally considered that the removal efficiency of HCl by a Ca–Mg–Al hydrothermal liquefaction (HTL) adsorbent at high temperature was significantly higher than that by CaO and NaHCO 3 adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…The compositions of LDHs have the general expression [M­(II) 1– x M­(III) x (OH) 2 ] x + (A n – ) x / n · m H 2 O, in which M­(II) and M­(III) are divalent and trivalent metallic cations located in the main layer, A n – is the interlayer anion, m is the number of interlayer water molecules, and x is the molar ratio of M 3+ /(M 2+ + M 3+ ). The dechlorination performance and optimum ratio of hydrotalcite-like compounds have been previously studied. Hydrotalcite-like composite is a good dechlorination adsorbent, especially in the water environment, but its dechlorination characteristics in a high-temperature gas environment are yet studied. In some literature studies, , the high-temperature dechlorination adsorbent for hydrotalcite-like materials was studied, including the preparation of the dechlorination adsorbent, adsorption test, cross-flow moving bed reactor, and numerical simulation. It was generally considered that the removal efficiency of HCl by a Ca–Mg–Al hydrothermal liquefaction (HTL) adsorbent at high temperature was significantly higher than that by CaO and NaHCO 3 adsorbents.…”
Section: Introductionmentioning
confidence: 99%